Effects of therapeutic alliance on patients with major depressive disorder: a literature review - Videtta, Giovanni; Busilacchi, Silvia; Bartoccioni, Giulia; Cirella, Luisa; Barone, Ylenia; Delvecchio, Giuseppe (Frontiers in Psychology, 2025)
Therapeutic alliance refers to the collaborative relationship between a therapist and a patient, a concept widely explored in clinical research. It has emerged as a crucial component of effective psychotherapeutic interventions, particularly in the treatment of major depressive disorder (MDD), where its role appears to be multifaceted. In this context, we reviewed the main literature on the role of therapeutic alliance in MDD. The record search was conducted across three databases: PubMed, Web of Science, and PsychInfo. Seven of the reviewed studies highlighted that therapeutic alliance is a strong predictor of clinical outcomes, contributing to symptom improvement, relapse prevention, and more adaptive functioning in patients with MDD. However, three studies supported the hypothesis that clinical improvement itself might influence the therapeutic alliance between a therapist and a patient at different stages of treatment. Overall, the results suggest a bidirectional relationship between therapeutic alliance and symptom improvement, indicating that a stronger alliance often predicts better outcomes and symptom reduction can further enhance the alliance. However, the interpretation of these results must consider certain methodological limitations. These include the use of different approaches, measurements, and clinical outcomes to assess therapeutic alliance, as well as insufficient exploration of the temporal precedence between therapeutic alliance and clinical outcomes. In conclusion, future studies are warranted to address these limitations and further clarify the role of therapeutic alliance in MDD, along with its potential implications for clinical practice.